OPPORTUNITIES FOR THE DEVELOPMENT OF INNOVATION AMONG HOTELS IN NORTHERN HUNGARY - Béla BENKŐ; Lóránt DAVID; Tibor FARKAS (Geo Journal of Tourism and Geosites, 2022)
The aim of the study is to analyse the various infrastructural developments of the tourism sector in Northern Hungary. The study examines the innovation potential and it’s obstacles of hotels in the region. The research is based on a survey of hotel managers, using Kruskal – Wallis tests as the main statistical method. The well-developed infrastructure and the effective adaptation and application of innovations are essential for the creation of complex tourism packages based on the tourist attractions of the region and thus contribute to the development of the region. The research confirms that tenders for development are more common in larger and more capital-intensive hotels. The smaller ones are excluded from the tender system partly due to the lack of qualified labour. There is progress in innovation; most people are currently implementing product / service innovation.